Foreign Aid and Economic Development in Indonesia - Askar, Media Wahyu (Jurnal Ilmiah Administrasi Publik, 2015)
It has been suggested that foreign aid can bring positive impact on economic development. However, in developing countries, such as Indonesia, the impacts of foreign aid program are mainly seen temporary. Instead, foreign aid has contributed to the growing of the real debt burdens. The lack of capital, however, should not be a reason for taking foreign aid in Indonesia. This problem is actually because the Indonesian Government is corrupt, inefficient and poorly managed